Development of Mystery Box Media to Teach Speaking Skill at Senior High School Students - Kholifatin, Umi; Makrifah, Istina Atul; Widiarini (IKIP Siliwangi, 2025)
This study focuses into the usefulness of Mystery Box media in helping students improve their English speaking skills, particularly in descriptive writing, at MA Syekh Subakir Nglegok, Grade 10 B. The research takes a Research and Development (R&D) strategy, employing both qualitative and quantitative approaches based on the ADDIE paradigm. Qualitative data were gathered through teacher interviews and expert validation, while quantitative data were gathered from pre-test and post-test scores, as well as Likert scale-based student satisfaction questionnaires. The results show an important rise in pupils' speaking performance, with average scores rising from 64.78% to 81.30%, a 16.52% increase. According to the Likert-scale questionnaire, 85% of students were satisfied with the media, indicating that they considered it engaging and effective. Expert validation demonstrates that the Mystery Box is viable, versatile, and useful for classroom use. However, some problems, such as diverse student involvement and vocabulary limits, were found.